Effectiveness and safety of herbal medicines for induction of labour: a systematic review and meta-analysis - Edward Fottrell; Carina King; Chrispin Mandiwa; Collins Zamawe; Hannah Maria Jennings (BMJ Open)
Objective The use of herbal medicines for induction of labour (IOL) is common globally and yet its effects are not well understood. We assessed the efficacy and safety of herbal medicines for IOL.Design Systematic review and meta-analysis of published literature.Data sources We searched in MEDLINE, AMED and CINAHL in April 2017, updated in June 2018.Eligibility criteria We considered experimental and non-experimental studies that compared relevant pregnancy outcomes between users and non-user of herbal medicines for IOL.Data extraction and synthesis Data were extracted by two reviewers using a standardised form. A random-effects model was used to synthesise effects sizes and heterogeneity was explored through I2 statistic. The risk of bias was assessed using ‘John Hopkins Nursing School Critical Appraisal Tool’ and ‘Cochrane Risk of Bias Tool’.Results A total of 1421 papers were identified through the searches, but only 10 were retained after eligibility and risk of bias assessments. The users of herbal medicine for IOL were significantly more likely to give birth within 24 hours than non-users (Risk Ratio (RR) 4.48; 95% CI 1.75 to 11.44). No significant difference in the incidence of caesarean section (RR 1.19; 95% CI 0.76 to 1.86), assisted vaginal delivery (RR 0.73; 95% CI 0.47 to 1.14), haemorrhage (RR 0.84; 95% CI 0.44 to 1.60), meconium-stained liquor (RR 1.20; 95% CI 0.65 to 2.23) and admission to nursery (RR 1.08; 95% CI 0.49 to 2.38) was found between users and non-users of herbal medicines for IOL.Conclusions The findings suggest that herbal medicines for IOL are effective, but there is inconclusive evidence of safety due to lack of good quality data. Thus, the use of herbal medicines for IOL should be avoided until safety issues are clarified. More studies are recommended to establish the safety of herbal medicines.